2010
DOI: 10.1007/s00249-010-0641-8
|View full text |Cite
|
Sign up to set email alerts
|

Ion fluxes, transmembrane potential, and osmotic stabilization: a new dynamic electrophysiological model for eukaryotic cells

Abstract: Survival of mammalian cells is achieved by tight control of cell volume, while transmembrane potential has been known to control many cellular functions since the seminal work of Hodgkin and Huxley. Regulation of cell volume and transmembrane potential have a wide range of implications in physiology, from neurological and cardiac disorders to cancer and muscle fatigue. Therefore, understanding the relationship between transmembrane potential, ion fluxes, and cell volume regulation has become of great interest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 24 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…A great contribution would be a clarification of the question whether voltage-gated 7 or other channels are involved in the signal transduction. This could lead to multiphysics models including, for example, ion dynamics 66 or the mechanical behavior of the membrane 53 , 67 . Furthermore, the adhesion of chondrocytes and resulting gaps between cell membrane and insulator should be investigated to provide reliable geometric models of cells in capacitive-coupling stimulation chambers.…”
Section: Discussionmentioning
confidence: 99%
“…A great contribution would be a clarification of the question whether voltage-gated 7 or other channels are involved in the signal transduction. This could lead to multiphysics models including, for example, ion dynamics 66 or the mechanical behavior of the membrane 53 , 67 . Furthermore, the adhesion of chondrocytes and resulting gaps between cell membrane and insulator should be investigated to provide reliable geometric models of cells in capacitive-coupling stimulation chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Far from being explanatory, the above-mentioned conceptual framework suggests the activation of control mechanisms for cell volume excursions not considered in the 2-parameter model. Borrowing from available literature, intracellular mechanisms involving ion-pumps and/or ion-channels could represent a possible candidate for explaining the observed osmotic behaviour [ 41 43 ]. However, it is worth noting that ion pumps work on relatively long time scales, not compatible with the rapid response to osmosis exhibited by hMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a stationary condition, passive ion fluxes are assumed to be compensated by opposing active fluxes that do not balance those generated during RVD. Active fluxes were assumed to be constant since several previous reports demonstrated that short-term volume regulation is not affected by them [25], [26].…”
Section: Methodsmentioning
confidence: 99%